The PolS-PolR Two-Component System Regulates Genes Involved in Poly-P Metabolism and Phosphate Transport in Microlunatus phosphovorus - Zhong, Chuanqing; Zhang, Peipei; Liu, Cheng; Liu, Meng; Chen, Wenbing; Fu, Jiafang; Qi, Xiaoyu; Cao, Guangxiang (Frontiers in Microbiology, 2019)
Microlunatus phosphovorus NM-1 is a polyphosphate (poly-P)-accumulating bacterium that accumulates poly-P under aerobic conditions and degrades poly-P under anaerobic conditions. In this study, the two-component system (TCS) PolS-PolR was identified in NM-1, and the response regulator PolR was found to directly bind to the promoters of genes related to phosphate transport (MLP_RS00235, MLP_RS23035 and MLP_RS24590); poly-P catabolism (MLP_RS12905) and poly-P synthesis (MLP_RS23025). RT-qPCR assays showed that ppgk (MLP_RS12905), ppk (MLP_RS23025), pstS (MLP_RS23035) and pit (MLP_RS24590) were down-regulated during the aerobic-anaerobic shift. The sequence GTTCACnnnnnGTTCaC was identified as a recognition sequence for PolR by MEME analysis and DNase I footprinting. EMSAs and ChIP-qPCR assays indicated that PolR binds to the promoters of pit (MLP_RS00235), ppgk (MLP_RS12905), ppk (MLP_RS23025), pstS (MLP_RS23035) and pit (MLP_RS24590), and ChIP-qPCR further suggested that the binding affinity of PolR was lower under anaerobic conditions than under aerobic conditions in vivo. These findings indicate that the PolS-PolR TCS in M. phosphovorus may be involved in the regulation of poly-P metabolism in response to levels of dissolved oxygen in the environment, and our results provide insights into new approaches for understanding the mechanisms of phosphorus accumulation and release.